Social Actors in The News of Iran's Attack on Israel in Mass Media: Theo Van Leeuwen's Critical Discourse Analysis - Rifki Mustofa; Moh Zawawi; Mellinda Raswari Jambak; Zaki Ghufron; Aulia Fadhila Wirmansyah (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2025)
The rising tensions between Iran and Israel have been highlighted by many international mass media, such as Al Arabiya, and BBC Araby. This research discusses mass media strategies in representing social actors in the news of Iran's attack on Israel using Theo Van Leeuwen's Critical Discourse Analysis model. The research method used is descriptive qualitative with data collection techniques including documentation, reading, and note-taking. Then the data analysis technique used is the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing. The researcher focused the analysis on inclusion strategies described by Theo Van Leeuwen, such as nomination, categorization, assimilation, association, determination, and others. The findings show that Al Arabiya, and BBC Araby media use four strategies to present the social actors involved in their news narratives about Iran's attack on Israel. The four strategies include determination, indetermination, assimilation, and individualization. Of the four strategies used, BBC Arabic media has a greater and more detailed representation of the details of the social actors involved than Al Arabiya media, it can be seen from the high percentage of BBC Araby media in highlighting the various social actors featured in each strategy in the news narrative.